Research Progress and Future Agendas on Just Transitions in Geography - Dong Ke; Hu Xiaohui; Liu Minsi (Redai dili)
To promote the implementation of the Paris Agreement and achieve the "Dual Carbon Goals", China aims to develop sustainability transitions in production, lifestyle, and consumption, shifting away from its current socio-technical system reliant on the petrochemical energy. Sustainability transitions involve replacing outdated technological systems with new ones. However, this process inevitably triggers negative social consequences, potentially exacerbating social injustice and inequalities. Therefore, the challenge of achieving a "spatially just transition" has become a key issue in economic geography. This study examines international (English-speaking) studies on sustainability transitions and particularly explores the background, themes, and characteristics of related geographical research through bibliometric analysis. The study found the following. (1) Research on transitions is characterized by a strong geographical emphasis. It originated in the early 21st Century from Western old industrial cities and resource-based regions, where the adoption of green technologies as a key mean for industrial transformation. While green technologies did alleviate environmental problems while it also brought about new social problems (such as, unemployment and poverty among traditional workers) and widened social injustices. (2) The concept of just transition currently lacks a unified definition, theoretical framework, and empirical viewpoints. Due to its late entry into the field, related research in geography remains on the periphery of mainstream academic discourse on just transition. In spite of that, geographical perspectives and concepts such as "place," "scale," and "spatiotemporal context" are gradually gaining recognition. (3) The theoretical discourse of just transition has been constructed and dominated by Western developed countries, with insufficient consideration and theoretical reflection on the practical experiences and contextual characteristics of developing countries and regions. However, as China is currently the world's largest driver of transition and a leading promoter of urban/regional pilot initiatives, the geography of just transition holds significant potential for empirical exploration and theoretical reconfiguration. This paper argues that Chinese geographers should seize the historical opportunity to focus on localized transition practices under national policy frameworks such as the Common Prosperity Strategy and the Ecological Civilization Construction. Particular attention should be paid to the transformation of peripheral and less-favored regions or "left-behind places"—such as old industrial areas, resource-dependent cities, and ecologically fragile regions—and their associated social justice challenges during green transitions. Moreover, just transition research should be positioned as a critical topic in current and future studies addressing regional uneven development.